The Expanded Role of Roof-Rats (Rattus rattus) in Salmonella spp. Contamination of a Commercial Layer Farm in East Japan - Camba, Sherwin I.; Del Valle, Fletcher P.; Umali, Dennis V.; Soma, Takehisa; Shirota, Kazutoshi; Katoh, Hiromitsu; Sasai, Kazumi (University Knowledge Digital Repository, 2021)
© 2020 Avian Diseases. All rights reserved. Rodents serve as amplifiers of Salmonella infections in poultry flocks and can serve as a source of Salmonella contamination in the environment even after thorough cleaning and disinfection. This study aims to determine the dynamics of Salmonella occurrence in rodents and its relation to Salmonella contamination in the layer farm environment, including air dusts and eggs. From 2008 to 2017, roof rats (Rattus rattus), environmental swabs, air dusts, and eggs were collected from an intensive commercial layer farm in East Japan and were tested for Salmonella spp. using standard procedures. In roof rat samples, the Salmonella isolation rate was reached at 10% (95% confidence interval [CI] 8.1-21.9) in which Salmonella Corvallis, Salmonella Infantis, Salmonella Potsdam, and Salmonella Mbandaka were the frequent isolates from the cecal portion of the intestines. On the other hand, the prevalence rate of Salmonella in environmental swabs was at 5.1% (95% CI 2.2-7.4) while air dusts were at 0.9% (95% CI 0.2-1.8). It was observed that the prevalence of predominant Salmonella serotypes shifted over time; in roof rats, it was noted that Salmonella Potsdam gradually replaced Salmonella Infantis. In environmental swabs and eggs, Salmonella Corvallis and Salmonella Potsdam increased significantly while Salmonella Infantis became less frequent. In air dusts, Salmonella Corvallis was observed to decrease and Salmonella Potsdam became more common. Based on our findings, the role of roof rats in the epidemiology of Salmonella in layer farms was expanded from being a reservoir and an amplifier host into a shifting vessel of the most predominant serotypes.